Primeiro encontro de Aedes (Stegomyia) albopictus (Skuse) no Estado do Paraná, Brasil First recorded occurrence of Aedes (Stegomyia) albopictus (Skuse) in the South-Eastern region of Brazil - Adson Luís Sant'Ana (Universidade de São Paulo, 1996)
Foi constatada a primeira ocorrência de Aedes (Stegomyia) albopictus (Skuse) na cidade de Curitiba, Paraná. A coleta foi realizada, utilizando um sugador e isca humana como atração. The first recorded occurrence of Aedes (Stegomyia) albopictus (Skuse) in Curitiba, Paraná, South of Brazil, was described. The collection was carried out by means of aspirator in human bait.